From Religious Understanding to Tradition: The Role of Tuan Gurus in the Fidyah Practice within the Sasak Muslim Community - Sainun, Sainun; Hakim, Muhammad Lutfi; Sugitanata, Arif (JURIS (Jurnal Ilmiah Syariah), 2024)
This study examines the tradition of fidyah payments—compensation for missed prayers (ṣalāt) on behalf of the deceased—within the Sasak Muslim community in Central Lombok, Indonesia. Although this practice diverges from the mainstream Shāfiʿī school of law (madhhab), which the community primarily follows, it endures as a deeply ingrained tradition. Based on fieldwork and interviews with tuan gurus (local religious leaders) and deceased family members, the research finds that fidyah is commonly paid using rice, money, or gold from the deceased’s estate, distributed as alms to the poor. The community views fidyah as a means of atoning for missed prayers, offering peace to the family. Tuan gurus legitimize this practice by citing specific Islamic juristic opinions, particularly those of Imām al-Subkī and Imām Abū Ḥanīfah. Over generations, the Sasak community has internalized fidyah as a communal obligation, with non-compliance regarded as a family dishonor. This study demonstrates how tuan gurus’ teachings shape and institutionalize religious practices, transforming them into essential cultural traditions.